Overloads and interferences as risk factors in periodontal disease. - Esther María Castillo Betancourt; Marta M. Bosch Pons; Bienvenido Mesa Reinaldo; Maricela Seijo Machado; Zahily Espino Otero (Medisur)
Background: Peridontal diseases are among the most common diseases affecting human beings, and are the second major buccal health problem worldwide. Objective: To assess the relation between occlusion overloads and interferences and periodontal disease severity. Method: Descriptive, retrospective analytical study of 100 patients who attended to the Periodontal Consultation in Cienfuegos Dental Clinic between January, 2002 and January, 2007, with diagnosis of periodontitis and occlusal overload and interferences. The variables were: periodontal pocket, gingival retraction, dental mobility, and differences between teeth groups with and without occlusal overload and interferences were determined, according to these variables. Results: There were significant differences between both groups (with and without overloads and interferences) regarding each variable. Conclusions: Our results show the relation between these two factors and periodontal disease.